2010
DOI: 10.1016/j.tcb.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Assembly, structure, and function of the 26S proteasome

Abstract: The 26S proteasome is a large multi-protein complex involved in the regulated degradation of ubiquitinated proteins in the cell. The 26S proteasome has been shown to control an increasing number of essential biochemical mechanisms of the cellular lifecycle including DNA synthesis, repair, transcription, translation and cell signal transduction. Concurrently, it is increasingly seen that malfunction of the ubiquitin proteasome system contributes to the pathogenesis of disease. The recent identification of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
179
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(185 citation statements)
references
References 111 publications
(174 reference statements)
1
179
0
1
Order By: Relevance
“…We utilized the epitope tag to monitor the steady-state incorporation of these proteins into 26 S proteasome and/or other pro- 2 The abbreviations used are: AMC, 7-amino-4-methylcoumarin; Suc, succinyl. tein complexes by glycerol density gradient centrifugation, as described above for endogenous proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We utilized the epitope tag to monitor the steady-state incorporation of these proteins into 26 S proteasome and/or other pro- 2 The abbreviations used are: AMC, 7-amino-4-methylcoumarin; Suc, succinyl. tein complexes by glycerol density gradient centrifugation, as described above for endogenous proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The lid partially surrounds the ATPase ring of the base, and two ubiquitin receptors, Rpn10 and Rpn13, are located on the periphery of the 19S RP [5][6][7][8] . Recent studies have suggested that the assembly of the proteasome proceeds via a highly ordered multistep mechanism [9][10][11][12] . All of the subcomplexes of the proteasome (CP, base, and lid) seem to assemble independently; the CP and base require multiple proteasome-dedicated chaperones for efficient and correct assembly.…”
mentioning
confidence: 99%
“…Successful self-assembly conditions had to be carefully worked out for the bacterial ribosome, 17,29 and corresponding conditions are unattainable for the eukaryotic ribosome, which requires as many as 200 accessory proteins in vivo, most of them essential. 30 Even lesscomplicated complexes, such as the nucleosome 31 or the proteasome, 32 require assisted assembly in the cell. Such examples illustrate a basic difference between the in vitro assembly of 20 isolated components, each introduced in a specific order under controlled conditions, and their in vivo assembly amidst a sea of competing components.…”
Section: Limitations Of Spontaneous Assembly From Isolated Proteinsmentioning
confidence: 99%